2021
DOI: 10.54209/infosains.v11i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Semi-public watermarking digital implementation in the concealment of text messages

Abstract: The purpose of this study is to generate watermarking of an input image. The watermarking process will begin with the process of reading color image pixels. After that, the process will be continued by calculating the  step message value inserted and inserting all the necessary values in the watermarking checking process. In the event of an attack, then at the time of watermarking formation, a specific noise value (randomly generated) will be calculated to be inserted into the image. After the process of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…We live in a world with limited resources struggling with an ever-increasing population. Hasto Wardoyo, Head of Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) also revealed that during the Covid-19 pandemic the birth rate was increasing (Info Public, 2021). Rapid population growth will lead to the consumption of large amounts of resources (Zhang & Ke, 2020).…”
Section: B As An Effort To Utilize Resources Efficiently and Effectivelymentioning
confidence: 99%
“…We live in a world with limited resources struggling with an ever-increasing population. Hasto Wardoyo, Head of Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) also revealed that during the Covid-19 pandemic the birth rate was increasing (Info Public, 2021). Rapid population growth will lead to the consumption of large amounts of resources (Zhang & Ke, 2020).…”
Section: B As An Effort To Utilize Resources Efficiently and Effectivelymentioning
confidence: 99%